2004
DOI: 10.1038/sj.ejcn.1601976
|View full text |Cite
|
Sign up to set email alerts
|

Influence of maternal serum levels of vitamins C and E during the second trimester on birth weight and length

Abstract: Objective: It has been known that maternal oxidative stress during pregnancy plays an important role in fetal growth. However, the association between antioxidant vitamin levels and birth outcomes is not conclusive. We investigated the relationship between maternal serum levels of vitamins C and E during the second trimester and birth weight and length. Design: Prospective cohort study. Setting: Outpatient-clinic of obstetrics, Ewha Womans University Hospital, South Korea. Subjects and methods: The study subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
35
1
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(44 citation statements)
references
References 45 publications
7
35
1
1
Order By: Relevance
“…Our findings are in concordance with Lee et al who demonstrated that pregnant women utilize a defence mechanism, which is composed of antioxidant-enzymes and nutrients including vitamins C and E, against oxidative stress and free radical damage and imbalance between increased oxidative stress and decreased antioxidant defences impairs fetal growth [37].…”
Section: Discussionsupporting
confidence: 93%
“…Our findings are in concordance with Lee et al who demonstrated that pregnant women utilize a defence mechanism, which is composed of antioxidant-enzymes and nutrients including vitamins C and E, against oxidative stress and free radical damage and imbalance between increased oxidative stress and decreased antioxidant defences impairs fetal growth [37].…”
Section: Discussionsupporting
confidence: 93%
“…), vitamin (i.e. vitamins A, C, and E), and folate deficiencies are known to contribute to abnormal prenatal development (36)(37)(38)(39). Furthermore, in this paper, maternal fasting plasma active GLP1 levels correlated positively and negatively with HDL-C during the first trimester of pregnancy and with triglycerides during the second trimester of pregnancy respectively.…”
Section: Discussionmentioning
confidence: 52%
“…36 Interestingly, several human studies have found a positive correlation between maternal plasma vitamin C concentrations and baby birth weight. 37 Intrauterine growth restriction accompanies Ϸ30% to 40% of cases of preeclampsia. Maternal concentrations of plasma ascorbate are low at 20 weeks of gestation and throughout the remainder of pregnancy, not only in women who develop preeclampsia during the third trimester but also in women who remain normotensive but deliver small-for-gestational-age neonates.…”
Section: Discussionmentioning
confidence: 99%